Importance of cuy in the high Andean region of the province of Huaral - van Dalen Luna, Pieter (2020)
This article presents a historical overview of the importance of guinea pigs in the peasant communities of the upper Chancay - Huaral river basin. This importance remains valid from the prehispanic period of the Late Intermediate (Atavillos culture), as it is appreciated in the archaeological evidences recovered in places like Rupac, Marca Piche, Purunmarca and Araro; Sites investigated with excavations in the last five years. Ethnohistoric sources also refer to the importance of this animal in the indigenous communities of the different parishes. At present, the importance of the guinea pig remains in force in the high Andean communities of the province of Huaral, with medicinal and nutritional purposes.